On the Oscillation Property for Some Nonlinear Differential Equations of Second Order - Fatima N. Ahmed, Aisha Dinar Ali (Journal of Pure & Applied Sciences, 2019)
In this paper, oscillatory behaviour of solutions of a class of nonlinear second-order ordinary differential equations is investigated. By using Riccati substitution technique, some new sufficient conditions for the oscillation are given. Comparisons between our results and the previously known results are presented. Furthermore, some illustrative examples are also included to show the evidence of the new results. However, results obtained here improve and/or extend some of well known results in the literature.